THE BENEFITS OF INTERNET IN LEARNING ENGLISH FOR ENGLISH DEPARTMENT STUDENT - Sinta Dewi Anggun (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2023)
This study aims to evaluate the perceptions related to the benefits of using the internet in English learning for fifth-semester students of the English Education Department. This research study used qualitative research. Instrument in this study was questionnaire, the data was collected from 15 statement items covering aspects such as the importance of the internet in learning, the benefits of using the internet, learning independence, improvement of language skills, and the positive impact of the internet in various language skills. There were 15 respondents who were asked to answer the questionnaire. Based on the questionnaire, the results showed that the majority of students agree that the internet is important in learning (73.3%) and provides significant benefits (60%). They also tend to agree that the internet improves learning independence (26.7%) and English language skills (33.3%). However, there were variations in perceptions regarding speaking and listening skills. Although most felt motivated by online content (46.7%), this study highlights the importance of developing teaching strategies that suit students' preferences and needs.